Experimental perspectives on spatial deictic expression acquisition in Thai - Chanchaochai, Nattanun; Schwarz, Florian (Proceedings of Sinn und Bedeutung, 2023)
This study explored the role of perspectives on the interpretation of Thai spatial deictic terms lˇaN ‘behind’ and nˆa: ‘in front of.’ We designed an experiment where the relative location of the experimenter and the participant differed across two sessions. Utilizing 5 objects of 5 different colors arranged in a row, the experimenter asked the participant ‘The pen/balloon of which color is behind/in front of the x pen/balloon?,’ where x is the color of one of the middle three items. Participants were native speakers of Thai, including 31 adults, 60 typically developing children, and 30 children with Autism Spectrum Disorders (ASD). We found that for Thai-speaking adults, the convention for 'behind/in front of' seems to involve object-based allocentric viewpoint, relativizing the deictic notions as if the objects were facing themselves. However, the relative location of the experimenter hugely affected the adults who started off sitting opposite to the experimenter. In contrast, children with TD, egocentric interpretations, projecting their own front and back onto the objects, are preferred for non-fronted, visible objects. Verbal questions and mere presence of Speaker, i.e., without gazes nor gestures, are enough to introduce ambiguities between FoRs for adults and children with TD. Despite their differences from adults in overall perspective resolution, TDs do take into account the experimenter’s viewpoint as a contextual resolution option. On the other hand, children with ASD were not affected by experimenter’s perspective, and lacked a clear contrast between the opposite deictic terms. They also seem to have general difficulties in grasping the basic relational nature of the two deictic terms.